Estandarización de los procesos productivos en la empresa agroproductiva “Avi Burz” - Mera Moreira, Lincol Eduardo (2023)
Currently the organizations have the need to be competitive in the markets, that is why the present investigation had the purpose of standardizing the productive processes of the "AviBurz" agro-productive company in Calceta city for the improvement of the production management. For this, in the first instance it was necessary to determine the methodology and the methods of which the inductive, deductive and synthetic analytical methods were used, it should be emphasized that these were necessarily used to carry out the respective analysis of the results obtained and the information collected during the course of the research. On the other hand, among the techniques used was the interview with the General Manager of this poultry company, which in turn helped to determine the internal and external factors that would be affecting the company, i.e., thanks to this technique it was possible to develop the SWOT matrix which is established in Chapter IV of this research. After that, experts were selected to help determine the key processes of the organization, among them: Ordering, Raw Material Reception, Milling, Mixing and Dispatch. In the same way, these experts contributed to the elaboration of the process manual, which has the purpose of contributing to the improvement of the production management of the "AviBurz" poultry farm.